The influence of lemongrass essential oil addition into heat cured acrylic resin against Candida albicans adhesion - Seineen S Al-Shammari; Faiza M Abdul-Ameer; Latifa R Bairam; Zeina Al-Salihi (College of Dentistry/ University of Baghdad, 2023)
Background: For decades, the use of naturally accessible materials in treating human disease has been widespread. The goal of this study was to determine the anti-fungal effectiveness /of the lemongrass essential oil (LGEO) versus Candida albicans (C. albicans) adhesion to polymethylmethacrylate (PMMA) materials. Material and methods: LGEO's anti-fungal activity was tested against C. albicans adhesion using the following concentration of LGEO in PMMA monomer (2.5 vol. %, 5 vol. % LGEO) selected from the pilot study as the best two effective concentrations. A total of 40 specimens were fabricated for the candida adherence test and were subdivided into four equal groups: negative control 0 vol. % addition, experimental with 2.5 vol. % and 5 vol. % of LGEO addition and positive control with 1.4 wt. % nystatin addition. The sterile PMMA specimens were incubated at room temperature for 1 hr in sterile tubes with a sabouraud dextrose broth (SDA) in which a small amount of the yeast was isolated and suspended; under the inverted light microscope, the examination was done. The data were evaluated using a one-way ANOVA test, which showed a significant result at p< 0.05. Results: The findings of the C. albicans adherence test exposed a considerable reduction in the number of C. albicans cells adhering to PMMA after adding 2.5 vol. % and 5 vol. % LGEO compared to specimens from the negative control and positive control groups at p< 0.05. Conclusion: Adding LGEO into a heat-cure acrylic material can result in a denture base material with anti-fungal properties versus C. albicans microorganisms. The experimental group 5 vol. % LGEO additive showed the best anti-fungal activity